Studying The Mahara Kitabah In Arabic - Arianto, Arianto; Koria, Koria; Mulyah, Santi (Lembaga Penelitian dan Pendidikan Mandala, 2026)
The goal of learning to read and write in Arabic is to enable students to write Arabic texts accurately, taking into account linguistic elements. Learning activities refer to achievement indicators, namely: (1) practice transcribing the sounds of words, phrases, and sentences; (2) practice answering questions based on reading texts and arranging them to form good paragraphs; and (3) practice expressing ideas or free writing using vocabulary appropriate to the given topic. Writing is a comprehensive linguistic skill that aims to produce what is called writing. Methodologically, in the learning process, especially in writing skills, the first thing that must be understood is understanding the purpose of learning to write itself, then defining it as a learning objective. It is important to understand the principles of learning to write so as not to deviate from the scope of discussion and evaluation.